2014
DOI: 10.1097/jnr.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effect of Work Excitement and Work Frustration on the Professional Commitment of Nurses in Taiwan

Abstract: Nurses often work in conditions that are highly frustrating. Although work excitement has been shown as having a greater influence on professional commitment when nurses experienced the dual work affects simultaneously, work frustration significantly reduces the professional commitment effect of nurses. This study suggests that managers should not only construct a positive and exciting work environment but also work to mitigate the causes of work frustration to promote professional commitment and retention amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…(), which has been confirmed to accurately measure senior nurses' feelings toward work (Chang et al . , ). The scale consisted of 17 questions assessed in three dimensions covering interpersonal interactions, resource use and work arrangement.…”
Section: Methodsmentioning
confidence: 97%
“…(), which has been confirmed to accurately measure senior nurses' feelings toward work (Chang et al . , ). The scale consisted of 17 questions assessed in three dimensions covering interpersonal interactions, resource use and work arrangement.…”
Section: Methodsmentioning
confidence: 97%
“…If nurses have more active and positive perceptions toward hospitals' social responsibility practices, they will have higher levels of identification with that hospital and tend to generate active and significant influences on job satisfaction and even organizational performance. In accordance with the suggestion of Chang, Wang, Huang, and Wang (2014), hospital managers should not only construct a positive and exciting work environment but also work to mitigate the causes of work frustration to promote professional commitment and retention among nurses. If nurses are recognized as crucial capital for hospitals and healthcare, hospital managers and government administrators must do more than merely comply with laws and regulations and make every effort to provide a friendly and humane work environments for nurses.…”
Section: Discussionmentioning
confidence: 62%
“…Informal workplace learning and professional support could help novice nurses to be better prepared for the clinical setting and to deal with complex care situations. Previous studies indicated that feedback, peer‐to‐peer intervision, being linked to a work supervisor and scheduled evaluation times are indispensable strategies to achieve this (Chang, Wang, Huang, & Wang, ; Parker et al., ). The finding of the study by Takase, Yamamoto, Sato, and Niitani () showed that the self‐reported competence of less experienced nurses was positively correlated to learning from others.…”
Section: Discussionmentioning
confidence: 99%